Bone Mineral Density in Ankylosing Spondylitis - Bahar Çakmak; Hidayet Sarı (Türk Osteoporoz Dergisi)
Ankylosing Spondylitis (AS), a chronic inflammatory rheumatic disease. One of the most frequent and important complications in these patients is osteoporosis. There are controversial studies on the correlation of osteoporosis and disease duration, activity and functional status. Twenty-one male and five female patients diagnosed as AS according to Modified New York, ESSG( European Spondyloartropaties Study Group) and Amor criteria were included in this study. Disease duration and age-sex of the patients was assessed. Patients with ankylosed lumbar spine in late stages of the disease were excluded. Bone mineral density (BMD) was measured by DEXA( Hologic) at lumbar and femoral neck regions. BASDAI was used for evaluation of disease activity and BASFI index for functional status evaluation.Correlation of BMD with disease duration, BASDAI and BASFI indexes was assessed. BMD at lumbar spine and femoral neck regions was found to be osteoporotic in 11,5 % of the patients. In the lumbar region there was no correlation between BMD and disease duration, BASFI and BASDAI indexes. BMD values of femoral neck showed a weak inverse correlation with disease duration, while no correlation was found between BMD and BASFI and BASDAI. As a conclusion in AS patients osteoporosis besides the disease itself many secondarily influence disease prognosis and complications. Therefore osteoporosis should be evaluated in the management and follow-up of AS patients.